Motivación y flow en deportistas de alto rendimiento de las Federaciones Ecuatorianas de levantamiento olímpico de pesas y patinaje - Calderón Guijarro, Karina Belén (2017)
This research project was carried out in the Ecuadorian Federations of Olympic Lifting of Weights and Skating with a sample of 25 athletes, with the objective of analyzing the motivation and the flow in athletes of high performance in these disciplines, because the theory explains that intrinsic motivation is a facilitator of the flow state experimentation, in turn, the type of motivation that these athletes presented was identified. In addition, the presence of the state of flow in the population was determined. The study is descriptive, not experimental, sectional, mixed design, since the variables were analyzed qualitatively when obtaining the values of frequencies and quantitative percentages. The psychological batteries used are the "Sports Motivation Scale" by Pelletier et al., 1995; Balaguer, Castillo, and Duda, 2003; 2007 and the "Jackson and Marsh Flow State Scale", (1996), which gave as results: 96% practice their sport by intrinsic motivation and 4% by extrinsic. 60% experienced a state of total flow in the execution of their physical activity, 36% partial flow and 4% flow zero. The statistical package SPSS version 24.0 (IBM) was used, the Tau_de Kendall test was applied and it was obtained that the correlation is not significant for having obtained a value of p = 0.53.